THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE DISCIPLINE IN WIYUNG SEJAHTERA HOSPITAL - Popy Puspitasari; Ratna Dwi Wulandari (The Indonesian Journal of Public Health, 2022)
Introduction: The quality of health services is an important aspect that determines the success of a hospital. Through performance, the role of human resources determines the success of a hospital. Efforts to determine employee performance need to be performed, one of which is by measuring employee discipline. The application of employee discipline is related to the role of the leader in directing his subordinates. The way leaders lead their subordinates is reflected in the leadership style applied. This study aimed to determine leadership style applied in Wiyung Sejahtera Hospital and its effect on the level of employee work discipline. Methods: This was a quantitative study with analytic observational research design. This study involved 80 employees working in Wiyung Sejahtera Hospital as a sample. All of the samples met the inclusion criteria as respondents. The independent variable in this research is leadership style and the dependent variable is the level of employee work discipline. Data were obtained through survey with questionnaire aids. Result: The results showed 31.25% of the leadership styles applied by the head of the unit was directive leadership styles. The results of the linear regression effect test indicate that the significance value was <α is 0,000 <0.1. The results of the linear regression analysis showed that leadership style had a regression coefficient of 0.311. Conclusion: In conclusion, leadership style applied has an effect of 90.9% on the level of employee work discipline.